2002
DOI: 10.1074/jbc.m202343200
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Regulation of the Classical and the Alternative Pathway for Bile Acid Synthesis in Human Liver

Abstract: It has been reported that there is a coordinate regulation of sterol 27-hydroxylase (CYP27A1) and cholesterol 7␣-hydroxylase (CYP7A1) in rats. Thus, the levels of the mRNA corresponding to these two enzymes were found to change in the same direction in rat liver and in isolated rat hepatocytes. In contrast, other groups have not seen such regulation of CYP27A1 in rabbit liver or in rat liver when using an activity assay. In the present work, the effect of bile acid treatment on human CYP27A1/luciferase reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…It has been reported that there is a coordinate regulation of sterol 27-hydroxylase (CYP27A1) and cholesterol 7α-hydroxylase (CYP7A1) by bile acids in rats [160][161][162]. In humans, however, there appears to be little or no coordinate regulation of CYP7A1 and CYP27A1 at the transcriptional level, and human CYP27A1 is not subject to a negative feedback control by bile acids [163]. The results underline that marked species differences may exist in mechanisms for control of synthesis of bile acids and cholesterol homeostasis.…”
Section: Regulationmentioning
confidence: 96%
“…It has been reported that there is a coordinate regulation of sterol 27-hydroxylase (CYP27A1) and cholesterol 7α-hydroxylase (CYP7A1) by bile acids in rats [160][161][162]. In humans, however, there appears to be little or no coordinate regulation of CYP7A1 and CYP27A1 at the transcriptional level, and human CYP27A1 is not subject to a negative feedback control by bile acids [163]. The results underline that marked species differences may exist in mechanisms for control of synthesis of bile acids and cholesterol homeostasis.…”
Section: Regulationmentioning
confidence: 96%
“…In contrast, high-level expression of CYP7A1 increases the mRNA expression of LDL-R in liver cells and decreases the concentration of circulating LDL-cholesterol even in LDL-R-deficient mice [8]. In human, CYP7A1 expression is induced by its substrate cholesterol and inhibited by negative feedback from bile acid [9]. …”
Section: Introductionmentioning
confidence: 99%
“…The metabolic basis behind this is unclear, but it is of interest to note that species differences have recently been described in the molecular regulation of bile acid synthesis. [57][58][59][60][61] Furthermore, there appear to be species differences in the plasma lipoprotein response to stimulation of bile acid synthesis in LDLR deficiency. 62 Thus, stimulation of cholesterol 7␣-hydroxylase by gene transfer, 63 GH treatment, 26 or interruption of bile acid intestinal uptake 45 lowers LDL cholesterol in LDLR-deficient knockout mice, whereas complete biliary diversion in homozygous FH does not lower plasma LDL.…”
Section: February 2004mentioning
confidence: 99%